SUMO Suppresses the Activity of the Jasmonic Acid Receptor CORONATINE INSENSITIVE1. Issue 9 (16th August 2018) - Srivastava, Anjil Kumar; Orosa, Beatriz; Singh, Prashant; Cummins, Ian; Walsh, Charlotte; Zhang, Cunjin; Grant, Murray; Roberts, Michael R.; Anand, Ganesh Srinivasan; Fitches, Elaine; Sadanandom, Ari
Abstract : Small Ubiquitin-like Modifier protein, SUMO, regulates jasmonic acid (JA) signaling by suppressing the JA receptor CORONATINE INSENSITIVE1 activity independently of JA levels. Abstract: Plants respond rapidly to sudden environmental cues, often responding prior to changes in the hormone levels that coordinate these responses. How this is achieved is not fully understood. The integrative role of the phytohormone jasmonic acid (JA) relies upon the plant's ability to control the levels of JASMONATE ZIM (JAZ) domain-containing repressor proteins. Here, we demonstrate that regardless of intrinsic JA levels, Small Ubiquitin-like Modifier (SUMO)-conjugated JAZ proteins inhibit the JA receptor CORONATINE INSENSITIVE1 (COI1) from mediating non-SUMOylated JAZ degradation. The SUMO-deconjugating proteases OVERLY TOLERANT TO SALT1 (OTS1) and OTS2 regulate JAZ protein SUMOylation and stability. The ots1 ots2 double mutants accumulate SUMOylated and non-SUMOylated JAZ repressor proteins but show no change in endogenous JA levels compared with wild-type plants. SUMO1-conjugated JAZ proteins bind to COI1 independently of the JA mimic coronatine. SUMO inhibits JAZ binding to COI1. We identify the SUMO interacting motif in COI1 and demonstrate that this is vital to SUMO-dependent inhibition of COI1. Necrotroph infection of Arabidopsis thaliana promotes SUMO protease degradation, and this increases JAZ SUMOylation and abundance, which in turn inhibits JA signaling. This study reveals a mechanism for rapidly regulating JA responses, allowing plants to adapt to environmental changes.